Penambahan Berbagai Konsentrasi Karagenan terhadap Karakteristik Fruit Leather Pepaya - Mohamad Zhaki; Noviar Harun; Faizah Hamzah (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2018)
This research aimed to determine the effect of adding different concentrations carrageenanon the quality of papaya fruit leather. This study used Completely Randomized Design (RAL) with 4 treatments and 4 replications. The treatments used for papaya fruit leather were K1 (carrageenan 0.4%), K2 (carrageenan 0.6%), K3 (carrageenan 0.8%) and K4 (carrageenan 1,0%). The data obtained were analyzed statistically using ANOVA and DNMRT at 5% level. The results showed that sugar concentration had significant effect on water content, ash content, crude fiber content, total sugar content and descriptive and hedonic sensory assessment. The selected treatment resulted in papaya fruit leather is K3 (carrageenan 0,8%) with water content characteristics 16.79%, ash content 1.29%, crude fiber content 2.62% and total sugar content 46.86%. Descriptive sensory assessment of colour 4,1(orange), flavor 3,07 (slightly papayaflavored), taste 4,07 (papaya tasting), texture 3,65 (lightly clay and compact) and hedonic assessment based on overall as favored by panelists with score 4,14. Keywords: papaya, fruit leather, carrageenan.